Integrating Restoration Practices With Productive Activities to Promote the Sustainable Management of Dry Forests Devoted to Livestock Raising - Cavallero, Laura; Zarate, Martín Horacio (Wiley, 2025)
Livestock raising provides a livelihood for millions of people who inhabit forests worldwide. However, browsing and trampling can disrupt the regeneration of tree species, compromising the persistence of native forests in the long term. Therefore, in this study, we assess low-cost restoration practices compatible with livestock production. Specifically, we tested the effect of thorny branch protection on the survival and growth of natural regeneration and nursery-grown saplings of Lithraea molleoides. Additionally, we evaluated the effect of hydrogel application on protected and unprotected L. molleoides nursery-grown saplings. Finally, we compared the survival and growth of protected and unprotected natural regeneration versus nursery-grown saplings. In three fields under different grazing pressures, we marked 105 L. molleoides seedlings < 40 cm height (we protected 69, whereas 36 remained unprotected). Also, we transplanted 120 saplings > 70 cm height that were randomly assigned to four treatments (protected-with- and without-hydrogel; unprotected-with- and without-hydrogel). The protection with thorny branches facilitated the growth of natural regeneration and nursery-grown saplings. However, the efficiency of this practice depended on the grazing pressure, being more effective in the field with lower grazing pressure. Hydrogel addition did not affect nursery-grown saplings survival or growth, suggesting that in our study system the main filter to L. molleoides regeneration is cattle browsing and trampling. Finally, protecting naturally recruited individuals was more effective than protecting nursery-grown saplings. The practice assessed in this study allows for combining restoring and producing activities rather than separating them, thereby adapting to the management objectives of land owners and incorporating human livelihood needs in restoration plans.